2020
DOI: 10.1097/mao.0000000000002887
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma Practice Patterns: An International Cross-specialty Survey

Abstract: Objective: To assess vestibular schwannoma (VS) practice patterns among providers. Study Design: Cross-sectional survey. Setting: 8th Quadrennial International Conference on Vestibular Schwannoma and Other CPA Tumors. Subjects: Clinicians who specialize in the management of VS. Main Outcome Measures: Responses to ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The last century has witnessed a dramatic evolution towards increasingly conservative management of sporadic vestibular schwannoma (VS) (1,2). The trend has continued over the most recent two decades, and observation with serial imaging now constitutes the most common initial strategy employed for most patients with small-or medium-sized tumors (3). Today, among unselected population-based cohorts, roughly 75% of newly diagnosed cases undergo at least an initial period of observation with serial imaging (4,5).…”
mentioning
confidence: 99%
“…The last century has witnessed a dramatic evolution towards increasingly conservative management of sporadic vestibular schwannoma (VS) (1,2). The trend has continued over the most recent two decades, and observation with serial imaging now constitutes the most common initial strategy employed for most patients with small-or medium-sized tumors (3). Today, among unselected population-based cohorts, roughly 75% of newly diagnosed cases undergo at least an initial period of observation with serial imaging (4,5).…”
mentioning
confidence: 99%
“…Here, we focused on previously resected tumors, but our current strategy for evaluating and treating small VSs is to follow up with serial MRI scans and audiological tests. Serial imaging is the most common initial strategy for slow-growing, especially small-sized VS with a length of less than 2 cm (6,11). Previous reports describing tumor size in the genetically analyzed sporadic VS samples reported that the mean size of their surgically removed tumors ranged from 24.8 to 31.0 mm in length (33)(34)(35)49) (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing number of VS patients, the traditional microsurgery treatment for VS via the retrosigmoid, middle cranial fossa, or translabyrinthine approach has decreased (5). Serial imaging is now the most common initial strategy for most patients with small-or medium-sized VS tumors (6).…”
Section: Introductionmentioning
confidence: 99%
“…Stemming from a significant evolution in patient presentation and a greater understanding of the natural history of the disease, there has been a shift in the focus of vestibular schwannoma (VS) outcomes from radical tumor removal to preserving function and maintaining quality of life. [1][2][3] Today, many patients are diagnosed with small tumors, good hearing, and minimal to no attributable symptoms. For example, a recent publication encompassing 40-year epidemiological data reported a shift from no intracanalicular tumors being diagnosed in the late 1970s to nearly 50% in 2015, and a mean overall tumor size of 26 mm in 1976 to 7 mm in 2015 for all tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Stemming from a significant evolution in patient presentation and a greater understanding of the natural history of the disease, there has been a shift in the focus of vestibular schwannoma (VS) outcomes from radical tumor removal to preserving function and maintaining quality of life 1–3 . Today, many patients are diagnosed with small tumors, good hearing, and minimal to no attributable symptoms.…”
Section: Introductionmentioning
confidence: 99%